2020
DOI: 10.1038/s41598-020-63047-y
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous optimization of parameters influencing organic mulch test using response surface methodology

Abstract: Wind erosion could be regarded as one of the most important phenomena especially in arid lands in the globe, which destroys vast areas with its rapid growth. Due to global droughts and climate change, vegetation is weakened and soil particles are more easily exposed to wind erosion. Today, various methods have been developed to control wind erosion. One of the most commonly used methods is the use of mulch. Mulch has several types (physical-chemical). The purpose of this research is to make organic mulch with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…These positive effects of oil-mulch treatment have probably resulted from three mechanisms include 1) stabilizing effects on sand dunes (Wuddivira et al, 2013), 2) decreasing water evaporation and preserving available soil moisture (Kowsar et al, 1969;Mulumba and Lal, 2008;Liu et al, 2020) and 3) increasing the rate of seedling survival (Akbarian and Mosavi, 2006) and germination (Farahpour et al, 2005;Jafarian, 2006). Arid and semi-arid regions are known as water-limited areas (Shojaei et al, 2020), and thereby, soil moisture is an important factor that controls the seedling germination, survival, and growth (Zhenghu et al, 2004). It has been reported that oil-mulch treatment could provide more benefits in encouraging seed germination than other tested sand stabilizers (Farahpour et al, 2005), mainly due to the presence of more soil moisture and temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These positive effects of oil-mulch treatment have probably resulted from three mechanisms include 1) stabilizing effects on sand dunes (Wuddivira et al, 2013), 2) decreasing water evaporation and preserving available soil moisture (Kowsar et al, 1969;Mulumba and Lal, 2008;Liu et al, 2020) and 3) increasing the rate of seedling survival (Akbarian and Mosavi, 2006) and germination (Farahpour et al, 2005;Jafarian, 2006). Arid and semi-arid regions are known as water-limited areas (Shojaei et al, 2020), and thereby, soil moisture is an important factor that controls the seedling germination, survival, and growth (Zhenghu et al, 2004). It has been reported that oil-mulch treatment could provide more benefits in encouraging seed germination than other tested sand stabilizers (Farahpour et al, 2005), mainly due to the presence of more soil moisture and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Mulches are natural or artificial materials and are used to protect the soil from the damage of various factors such as wind and rain (Refahi, 2009). Oil (petroleum) mulch (hereafter oil-mulch) is one of the high-cost chemical mulches which can be sprayed over sand dunes to assist with re-vegetation (Amiraslani and Dragovich, 2011) and referes to oil products which are made of hydrocarbon mixtures and are used to cement sand particles (more details in Shojaei et al, 2020). Application or spraying of oil-mulches on the degraded and exposed soil to erosion reduces water evaporation (Chen et al, 2007), resulting in soil moisture manitenance and preventing sudden temperature changes (Ramakrishna et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To show the full impacts of adsorption, RSM can be used to maximize or minimize the output response and analyze the factor interactions [32]. The adsorption performance was optimized by CCD based on RSM.…”
Section: Experimental Optimization Of Adsorptionmentioning
confidence: 99%
“…To achieve optimal conditions by this method, the tests must be repeated for all factors, which leads to a very large increase in the number of tests. In order to cope with the limitations, various experimental design methods based on mathematical and statistical techniques have been developed, including the Taguchi method and response surface methodology (RSM) [34,35]. Taguchi method includes experimental design method to determine the effect of factors on the response and to obtain the optimal process conditions.…”
Section: Introductionmentioning
confidence: 99%